The Impact of Accounting Students' Competencies and Information Technology Adoption on Financial Reporting Quality (A Study at Universitas 17 Agustus 1945 Surabaya) - Friska Dhea Narulita; Adiati Trihastuti (Journal of Economics, Assets, and Evaluation, 2025)
This study aims to analyze the effect of accounting students’ competence and information technology utilization on the quality of financial reports among students of the Accounting Study Program at Universitas 17 Agustus 1945 Surabaya. This study uses a quantitative approach with a Likert scale-based questionnaire instrument. The research population consisted of 422 active students from the 2022–2024 cohorts, and the sample was determined using purposive sampling, resulting in 85 respondents. Primary data was obtained through the distribution of questionnaires, while data analysis was performed using multiple linear regression with the help of SPSS version 26. The results showed that accounting student competency had a positive and significant effect on the quality of financial statements. This is evidenced by a significance value of 0.000 < 0.05 and a t-value of 4.379 > 1.644. The use of information technology also has a positive and significant effect, with a significance value of 0.008 < 0.05 and a t-value of 2.730 > 1.644. Simultaneously, accounting student competency and information technology utilization have a significant effect on financial statement quality, as indicated by an F test significance value of 0.000 < 0.05 and an F count of 42.825 > 3.108. These findings indicate that the higher the level of student competence and the more optimal the use of information technology, the better the quality of the financial reports produced. This study contributes to strengthening the understanding of the importance of combining technical skills and the use of technology in the accounting learning process. The implications of this study are expected to serve as evaluation material for universities in improving the quality of learning, especially in the aspects of accounting practice and information technology integration.